The changes of fibroblast and periodontal ligament characteristics in orthodontic tooth movement with adjuvant HBOT and propolis: A study in Guinea pigs - Prayogo, Rosiana Dewi; Sandy, Bunga Novita; Sujarwo, Hendy; Fitri, Karimatul; Brahmanta, Arya; Rahardjo, Pambudi; Handayani, Budi (Padjadjaran Journal of Dentistry, 2020)
Introduction: Periodontal ligament plays an essential role in preventing relapse after orthodontic treatment. Hyperbaric Oxygen Therapy (HBOT) and propolis gel can increase the amount of fibroblast in the tension area during orthodontic treatment, thus affecting the periodontal ligament. This research was aimed to analyse the difference of the width of the periodontal ligament and amount of fibroblast in the tension area with the administration of propolis gel and HBOT in an attempt to prevent orthodontic relapse. Methods: Forty-two male guinea pigs were randomly divided into 7 groups of treatments― the untreated group (I – negative group), group with rubber separator (II – positive group), 3% propolis gel treatment group (III), 5% propolis gel treatment group (IV), the HBOT treatment group (V), combination of 3% propolis gel and HBOT treatment group, and combination of 5% propolis gel and HBOT treatment group. The upper left central incisor was extracted distally using a 14-days separator rubber in the positive group and the treatment group; then the separator rubber was removed for 2 days to conduct the relapse process. The data were analysed by LSD statistical test. Results: The result of the combination of HBOT and propolis gel treatment showed significant differences among all groups (p<0.05) in the width of the periodontal ligament (1.03), and the number of fibroblasts was 95.67 in the tension site. Conclusions: The combination of HBOT and propolis gel affect the width of periodontal ligament and the number of fibroblasts in the area of the orthodontic relapse.